2009
DOI: 10.1007/s00432-009-0701-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical study of recombinant adenovirus-p53 combined with fractionated stereotactic radiotherapy for hepatocellular carcinoma

Abstract: These results suggest that rAd-p53 combined with fSRT is a relatively safe and effective method for treating primary hepatocellular carcinoma compared with only fSRT. Thus, rAd-p53 combined with fractionated SRT may be preferred as a choice of local treatment for primary HCC when the patients are inoperable or when the patients refuse operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 14 publications
0
51
0
1
Order By: Relevance
“…For example, Chen et al (26) demonstrated that p53-induced microRNA-107 inhibited brain tumor cell growth, which indicates that it serves as a tumor suppressor and thus, may be used as a target for glioma therapy. Additionally, Yang et al (27) suggested a combination of recombinant adenovirus-p53 (rAd-p53) with fractionated stereotactic radiotherapy (fSRT) is an effective and relatively safe method for the treatment of primary hepatocellular carcinoma (HCC) compared with fSRT monotherapy, indicating that rAd-p53 combined with fSRT may be preferred as a local method to treat primary HCC if the patients are unable to undergo surgery or refuse operation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Chen et al (26) demonstrated that p53-induced microRNA-107 inhibited brain tumor cell growth, which indicates that it serves as a tumor suppressor and thus, may be used as a target for glioma therapy. Additionally, Yang et al (27) suggested a combination of recombinant adenovirus-p53 (rAd-p53) with fractionated stereotactic radiotherapy (fSRT) is an effective and relatively safe method for the treatment of primary hepatocellular carcinoma (HCC) compared with fSRT monotherapy, indicating that rAd-p53 combined with fSRT may be preferred as a local method to treat primary HCC if the patients are unable to undergo surgery or refuse operation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a recombinant human adenovirus that expresses functional wild-type p53 has been approved by the Chinese government for the treatment of head and neck carcinoma (48)(49)(50). Treatments showed that antitumor efficacy was associated with the expression and activity of functional p53, and adverse effects were also significant (51)(52)(53)(54). Recently, pharmacologically activated wild-type p53 by small-molecule compound RITA is …”
Section: Current Strategies To Target the P53 Pathway In Tumor Metabomentioning
confidence: 99%
“…Despite the lack of randomized controlled trials, radiotherapy is becoming recognized as a potentially curative treatment option (13). Conformal radiotherapy (CRT) for HCC was reported to exert a significant effect (14)(15)(16), as was SBRT (17)(18)(19)(20). However, the number of studies on the application of CRT and SBRT for the treatment of huge HCCs is limited.…”
Section: Introductionmentioning
confidence: 99%